2000
DOI: 10.1021/ol006746j
|View full text |Cite
|
Sign up to set email alerts
|

Sulfanyl- and Selanyldifluoromethylphosphonates as a Source of Phosphonodifluoromethyl Radicals and Their Addition onto Alkenes

Abstract: [figure: see text] Two different strategies are shown to produce sulfanyl and selanyldifluoromethylphosphonates. Thus, treatment of sulfanyldichloromethylphosphonates by 3HF.NEt3 in the presence of zinc bromide produces the corresponding sulfanyldifluoromethylphosphonates. In addition, lithiation of difluoromethylphosphonates followed by quenching with phenylsulfanyl chloride, phenylselanyl chloride, or diphenyl diselenide yields the corresponding sulfanyl- and selanyldifluorophosphonates. Generation of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Therefore, the reaction is highly regioselective. Similar regioselective addition of a difluorophosphonate radical to 2,3-dihydrofuran has recently been reported [15]. Although this reaction seems to be radical reaction, the product selectivity was appreciably affected by solvents used.…”
Section: Photolysis Of Ethyl Aa-difluoro-a-(phenylseleno)acetate (3)supporting
confidence: 78%
“…Therefore, the reaction is highly regioselective. Similar regioselective addition of a difluorophosphonate radical to 2,3-dihydrofuran has recently been reported [15]. Although this reaction seems to be radical reaction, the product selectivity was appreciably affected by solvents used.…”
Section: Photolysis Of Ethyl Aa-difluoro-a-(phenylseleno)acetate (3)supporting
confidence: 78%
“…Fuchigami and co-workers investigated the photoinduced S-CF 2 bond cleavage of various a,a-difluorinated sulfides in order to generate corresponding difluoromethyl radicals, which could be trapped with various unsaturated compounds [8a]. Lequeux et al reported the homolytic cleavage of the S-CF 2 bond of sulfanyldifluoromethylphosphonate using AIBN/n-Bu 3 SnH in the presence of various olefins to provide unsaturated difluoromethylphosphonate adducts [9]. Moreover, these authors and Eto et al used a,adifluoroalkyl aryl thioethers as building blocks for the synthesis of acrylthionucleosides [10] and 1,2,4-triazoles with a difluoro substituted sulfonylmethylene unit [11].…”
Section: Introductionmentioning
confidence: 99%
“…We showed that the chlore-fluor exchange can be performed with the non-corrosive 3HF-NEt3 complex in the presence of zinc bromide. This method allows to prepare alkylsulfanyl α,α-difluoromethylphosphonate in good yields (scheme 15), as new sources of both phosphonodifluoromethyl free radical and carbanion (15,57). …”
Section: Scheme 13mentioning
confidence: 99%